2014
DOI: 10.4137/mbi.s20618
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Allelic Frequency of Glutamate-Rich Protein (GLURP) inPlasmodium falciparumIsolates from Sub-Saharan Africa

Abstract: Glutamate-rich protein is a Plasmodium falciparum (Pf) antigen found in all stages of the parasite and has been reported to induce clinical immunity. The R0 and R2 regions have been found to exhibit a high degree of conservation, therefore serving as a good vaccine design material. We assayed the genetic diversity of Pf glurp genes in the R0 and R2 regions, as well as evaluated the role of seasonality on allelic frequency. A total of 402 genomic DNA samples, extracted from filter paper blood samples, were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Geometric mean MOIs for msp1 and msp2 of 1.90 and 1.88 were slightly lower than obtained in an earlier report from the middle belt of Ghana where MOI was 2.3 in July/August, [52] but similar to another report of MOI in southern Ghana which was 1.93 [24] and 1.3 in 2013 [53]. This discrepancy may be due to differences in ecological zones [54], malaria transmission intensity [36, 55] and/or the treatment-seeking behaviour of malaria patients within the various population [56, 57]. …”
Section: Discussionsupporting
confidence: 61%
“…Geometric mean MOIs for msp1 and msp2 of 1.90 and 1.88 were slightly lower than obtained in an earlier report from the middle belt of Ghana where MOI was 2.3 in July/August, [52] but similar to another report of MOI in southern Ghana which was 1.93 [24] and 1.3 in 2013 [53]. This discrepancy may be due to differences in ecological zones [54], malaria transmission intensity [36, 55] and/or the treatment-seeking behaviour of malaria patients within the various population [56, 57]. …”
Section: Discussionsupporting
confidence: 61%
“…The adoption of capillary electrophoresis (CE)-based sizing of PCR products largely resolved limitations of gel-based sizing protocols, such as insufficient resolution of minimal size differences, particularly among fragments larger than 500 bp, or unequal loading of variable PCR yields leading to apparent but artificial size differences. These limitations are particularly relevant for glurp genotyping, since amplicons of the glurp R2 region often surpass 1,000 bp in size, and CE-based glurp genotyping was not routinely used in most laboratories (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…33 However, the GLURP gene displays some antigenic diversity, with differing allelic variants, depending on geography and transmission intensity. 34 A previous report originating from our study area has revealed extensive genetic diversity in the MSP2 gene. 35 To expand our understanding of rsu3 rsu1 rsu2 rsu1 6 (46) 5 (46) rsu3 rsu2 rsu2 rsu1 2 (15) 1 (9) rsu3 rsu2 rsu3 rsu1 1 (8) 0 (0) rsu3 rsu2 rsu2 rsu3 2 (15) 0 (0) rsu3 rsu2 rsu1 rsu2 1 (8) 1 (9) rsu3 rsu1 rsu3 rsu1 1 (8) 0 (0) rsu3 rsu2 rsu2 rsu2 0 (0) 3 (27) rsu3 rsu1 rsu1 rsu1 0 (0) 1 (9) the genetic structure of P. falciparum and delineate potential contribution of ACT to malaria transmission intensity, we analyzed the parasite's GLURP R2 diversity in field isolates collected 12 years since artemisinin-combination therapy was introduced for the treatment of clinical malaria in Nigeria.…”
Section: Discussionmentioning
confidence: 72%
“…39 The observation of a considerable number of different GLURP genotypes in our study demonstrates its extensive diversity, with our finding being in agreement with previous studies which correlated genetic diversity with disease transmission intensity. 34,40,41 Malaria parasites use their extensive genetic diversity to their advantage as variability confers the ability to evade human immune responses, compromising vaccine efficacy and that of antimalarial drugs.…”
Section: Discussionmentioning
confidence: 99%